Single-molecule magnet behavior in 2,2’-bipyrimidine-bridged dilanthanide complexes - Yu, Wen; Schramm, Frank; Pineda, Eufemio Moreno; Lan, Yanhua; Fuhr, Olaf; Chen, Jinjie; Isshiki, Hironari; Wernsdorfer, Wolfgang; Wulfhekel, Wulf; Ruben, Mario (Beilstein Journal of Nanotechnology, 2016)
A series of 2,2’-bipyrimidine-bridged dinuclear lanthanide complexes with the general formula [Ln(tmhd)3]2bpm (tmhd = 2,2,6,6-tetramethyl-3,5-heptanedionate, bpm = 2,2’-bipyrimidine, Ln = Gd(III), 1; Tb(III), 2; Dy(III), 3; Ho(III), 4 and Er(III), 5) has been synthesized and characterized. Sublimation of [Tb(tmhd)3]2bpm onto a Au(111) surface leads to the formation of a homogeneous film with hexagonal pattern, which was studied by scanning tunneling microscopy (STM). The bulk magnetic properties of all complexes have been studied comprehensively. The dynamic magnetic behavior of the Dy(III) and Er(III) compounds clearly exhibits single molecule magnet (SMM) characteristics with an energy barrier of 97 and 25 K, respectively. Moreover, micro-SQUID measurements on single crystals confirm their SMM behavior with the presence of hysteresis loops.
Keywords: bipyrimidine; diketone; hysteresis; lanthanide; magnetism